IMPLEMENTATION AND LEADERSHIP OF EDUCATIONAL TASKS IN NON-GOVERNMENT PRESCHOOL EDUCATIONAL ORGANIZATIONS (Academia Science Repository, 2023)
This article discusses the organization and management of educational tasks in non-governmental preschool educational organizations.